Geschichtsunterricht de-zentrieren Globale Verflechtungen historisch denken lernen - Schwabe, Nicole (Ensayos InterAmericanos, 2020)
Global-historical approaches plead for the overcoming of national-historical traditions. This is accompanied by the demand to consciously reflect on the long-suppressed category of space in historical research. While there are signs of a rethinking in this context in the academic landscape, a national narrative continues to dominate in history lessons, both at the curricular level, but also in the planning of teaching units and materials for the classroom. With a view to the teaching of history in Germany, the call for a de-centering of historical learning provides suggestions as to how globally networked thinking can be promoted in the classroom. The starting point of these considerations is the teaching material series 'Wissen um globale Verflechtungen' ('Knowledge of Global Interconnections').